Recurrent Sigmoid Volvulus Associated With Eventration of Diaphragm in a Twenty-Six-Year-Old Man - Prabhu, Shailesh Mukund (Iran J Radiol, 2015)
Recurrent sigmoid volvulus is a clinical entity characterized by recurrent episodes of partial or complete sigmoid volvulus. Although it is commonly seen in the elderly, it can be occasionally seen in younger patients. Patients with recurrent partial sigmoid volvulus are relatively asymptomatic or present with mild abdominal pain. Early diagnosis and treatment is essential to prevent conversion to acute gangrenous volvulus. We present a case of recurrent partial sigmoid volvulus in association with eventration of diaphragm in a 26-year-old man.